Perancangan Desain Interface Sistem Informasi Bed Management Rawat Inap di RS Universitas Airlangga Surabaya - Ahmad Shofi Nur Kholili; Novita Nuraini; Rosita Prananingtias (Politeknik Negeri Jember, 2022)
Bed management is an inpatient bed processing activity by taking into account the 4 indicators of BOR, LOS, TOI and BTO. Based on observations, known that the number of inpatients from October - December 2021 continues to increase while the inpatient registration officers is only 1 officer. The bed management system is also still done manually. The purpose of this study was to design an information system interface design for Inpatient Bed management. The type of research used was the design of the bed management information system interface design. The method used was the prototype method with interview, observation and documentation data collection methods. The result was the design of the bed management information system interface that is tailored to the User's needs. The interface design can display room details to patients by showing facilities and room descriptions obtained by patients when treated according to the desired class, Users can also view and print the required reports including; inpatient visit reports, patient reports per payment type, and barber johnson indicator reports and this system can show graphs of total patient visits per room, graphs of total patient visits type of payment, and graphs of the number of patients per room.